Occurrence and Impact of Minor Histocompatibility Antigens' Disparities on Outcomes of Hematopoietic Stem Cell Transplantation from HLA-Matched Sibling Donors. (8th November 2012) - Dzierzak-Mietla, Monika; Markiewicz, M.; Siekiera, Urszula; Mizia, Sylwia; Koclega, Anna; Zielinska, Patrycja; Sobczyk-Kruszelnicka, Malgorzata; Kyrcz-Krzemien, Slawomira
Abstract : We have examined the alleles of eleven minor histocompatibility antigens (MiHAs) and investigated the occurrence of immunogenic MiHA disparities in 62 recipients of allogeneic hematopoietic cell transplantation (allo-HCT) with myeloablative conditioning performed between 2000 and 2008 and in their HLA-matched sibling donors. Immunogenic MiHA mismatches were detected in 42 donor-recipient pairs: in 29% MiHA was mismatched in HVG direction, in another 29% in GVH direction; bidirectional MiHA disparity was detected in 10% and no MiHA mismatches in 32%. Patients with GVH-directed HY mismatches had lower both overall survival and disease-free survival at 3 years than patients with compatible HY; also higher incidence of both severe acute GvHD and extensive chronic GVHD was observed in patients with GVH-directed HY mismatch. On contrary, GVH-directed mismatches of autosomally encoded MiHAs had no negative effect on overall survival. Results of our study help to understand why posttransplant courses of allo-HCT from siblings may vary despite the complete high-resolution HLA matching of a donor and a recipient.